2014
DOI: 10.1590/s0100-69162014000500015
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of Brazil nuts

Abstract: ABSTRACT:The Brazil-nut, also known as Para-nut, is widely used as food and in cosmetic industries. The seeds are rich in lipids and protein, and also present a considerable amount of selenium. Limited research has been conducted on postharvest of the Brazil nut, being an important information to design equipment related to aeration, drying, storage and transportation steps. Thus, the objective of this study was to determine the physical properties of the Brazil-nut with and without tegument. The dimensions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 2 publications
(1 reference statement)
1
11
0
1
Order By: Relevance
“…Guapeva seed has protein and lipid content higher than that found for its pulp and bark (table 1), corroborating what has already been described in literature regarding the considerable amounts of lipids and proteins for seeds and nuts that, as a result, are good energy sources (NOGueIRA et al, 2014). the estimated total carbohydrate content (Table 1) was higher in guapeva seed and was similar to that of raw pequi seed (35 mg.100g -1 ) and higher than that of raw baru nut (DANIANI et al, 2013;SIQUEIRA et.…”
supporting
confidence: 89%
“…Guapeva seed has protein and lipid content higher than that found for its pulp and bark (table 1), corroborating what has already been described in literature regarding the considerable amounts of lipids and proteins for seeds and nuts that, as a result, are good energy sources (NOGueIRA et al, 2014). the estimated total carbohydrate content (Table 1) was higher in guapeva seed and was similar to that of raw pequi seed (35 mg.100g -1 ) and higher than that of raw baru nut (DANIANI et al, 2013;SIQUEIRA et.…”
supporting
confidence: 89%
“…However, the Itaúba seeds presented the lowest values for the highest (a) and lowest (c) dimension characteristics of the seeds, meaning the length and thickness, respectively, as presented in Table 2. In studying the physical properties of Brazil nut seeds harvested in the municipality of Itaúba, Nogueira et al (2014) found values higher than these, being about 39.35 mm for the largest (a) and 17.88 mm for the smaller (c) characteristic sizes of the seeds.…”
Section: Resultsmentioning
confidence: 80%
“…done in the forest (NOGUEIRA et al, 2014) until the product commercialization (3.73% w.b.) phase (ÁLVARES et al, 2012).…”
Section: Discussionmentioning
confidence: 99%